Realization of Values: Stages of Meaningful Living for Hafiz Quran Students - Nasution, Nayla Afna Sa’adah; Nasution, Adelina; Nasution, Ismail Fahmi Arrauf (Psikis : Jurnal Psikologi Islami, 2024)
This study aimed to analyze the journey of finding meaning in life, focusing on the transformation from students’ meaningless inner feelings into meaningful feelings. This research is a field study with qualitative and phenomenological approaches. It involved six respondents with an average age of 17-18 years old. It examines the meaningfulness of life for students (santri) from the perspectives of the presence of meaning and the search for meaning. The results showed that childhood is a golden period for happiness, especially with parental support. However, orphans often lose motivation and a sense of meaning in life, feeling more pressured in boarding schools with the monotonous routine of memorizing the Qur'an. Students often pursue this education due to family pressure. In conclusion, the journey to find meaning in life for hafiz Qur’an students involves stages of suffering, self-acceptance, discovering the meaning of life, realizing that meaning, and leading a meaningful life.